PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERPERSPEKSTIF ISLAM RAHMATAN LIL ’ALAMIN ( IRA) : Studi Penanaman Nilai-Nilai Pendidikan Multikultural Di SMA Negeri 1 Ponorogo - Kasmui Kasmui; Happy Susanto; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2019)
This study examines the role and about the lack of education in implementing an integrated learning in the attitude of values namely; matter (mutual, cooperative, tolerant, peaceful, and the importance of mutually cherish each other as citizens of Indonesia. So much happening the case split either internally or fellow adherents of Islam to other faiths or externally, there is even an indication of students embraced the radical leftism. Then the researchers in terms of giving the title of the research